Predictors of hypoglycemia in insulin-treated patients with type 2 diabetes mellitus in Basrah - Nassar, Dhuha Tarik (World J Diabetes, 2016)
AIM: To measure the incidence and determinants (predictors) of hypoglycemia among patients with type 2 diabetes mellitus (T2DM) who were on insulin treatment for at least one year. METHODS: The present study is an out-patients based inquiry about the risk and predictors of hypoglycemia among patients with T2DM seeking care at the Al-Faiha Specialized Diabetes, Endocrine, and Metabolism Center, in Basrah over a period of 7 mo (from 15(th) of April, 2013 to 15(th) of October, 2013). The data used in the study were based on all detailed interview and selected laboratory investigations. A total of 336 patients could be included in the study. RESULTS: The incidence of overall hypoglycemia among the studied patients was 75.3% within the last 3 mo preceding the interview. The incidence of hypoglycemia subtypes were 10.2% for severe hypoglycemia requiring medical assistance in the hospital, 44.36% for severe hypoglycemia treated at home by family; this includes both confirmed severe hypoglycemia with an incidence rate of 14.6% and unconfirmed severe hypoglycemia for which incidence rate was 29.76%. Regarding mild self-treated hypoglycemia, the incidence of confirmed mild hypoglycemia was 21.42%, for unconfirmed mild hypoglycemia the incidence rate was 50.0% and for total mild hypoglycemia, the incidence rate was 71.42%. The most important predictors of hypoglycemia were a peripheral residence, increasing knowledge of hypoglycemia symptoms, in availability and increasing frequency of self-monitoring blood glucose, the presence of peripheral neuropathy, higher diastolic blood pressure, and lower Hemoglobin A1c. CONCLUSION: Hypoglycemia is very common among insulin-treated patients with T2DM in Basrah. It was possible to identify some important predictors of hypoglycemia.